Penguatan Mitigasi Bencana melalui Board Game Edukatif bagi Mahasiswa Semester Satu Universitas Syiah Kuala - Kamaly, Nurul; Dzakhi Ry, Mohd; Manora, Elsa; Helmi, Helmi; Faraidiany, Maghfira; Afrijal, Afrijal (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service focuses on increasing disaster literacy among first semester students by utilizing board games as an educational tool. The main issue raised was the students' lack of understanding about disaster mitigation and their lack of active involvement in educational activities. Through a community development approach, this activity was carried out in three stages: observation and planning, implementation of educational games, and evaluation using questionnaires. A total of 10 Syiah Kuala University students were involved in this activity. The evaluation results showed that 80% of the participants stated that the game was very easy to understand, while 70% of the participants considered that the appearance of the game was attractive. These results indicate that board games are an effective medium to convey disaster information in an interactive and fun way. Thus, this service is expected to increase collective awareness and encourage active participation of students in disaster risk reduction.